2014
DOI: 10.1039/c3cs60251f
|View full text |Cite
|
Sign up to set email alerts
|

The gold–hydrogen bond, Au–H, and the hydrogen bond to gold, Au⋯H–X

Abstract: In the first part of this review, the characteristics of Au-H bonds in gold hydrides are reviewed including the data of recently prepared stable organometallic complexes with gold(I) and gold(III) centers. In the second part, the reports are summarized where authors have tried to provide evidence for hydrogen bonds to gold of the type Au∙∙∙H-X. Such interactions have been proposed for gold atoms in the Au(-I), Au(0), Au(I), and Au(III) oxidation states as hydrogen bonding acceptors and H-X units with X = O, N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
207
2
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(226 citation statements)
references
References 234 publications
(376 reference statements)
4
207
2
13
Order By: Relevance
“…For the interaction with hydrogen atoms, plenty of examples of close contacts with hydrogen atoms have been reported in the crystal structures of Au – , Au + , and Au 3+ complexes 20 . However, as claimed in a recent review by Schmidbaur et al, the reported contacts are mostly due to the ligand-counterion interaction and/or crystal packing rather than the attractive interactions between Au and H atoms.…”
Section: Introductionmentioning
confidence: 99%
“…For the interaction with hydrogen atoms, plenty of examples of close contacts with hydrogen atoms have been reported in the crystal structures of Au – , Au + , and Au 3+ complexes 20 . However, as claimed in a recent review by Schmidbaur et al, the reported contacts are mostly due to the ligand-counterion interaction and/or crystal packing rather than the attractive interactions between Au and H atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Given the coordinative saturation of square‐planar gold(III) compounds and the reluctance of these complexes to bind a fifth ligand, the mechanistic aspects of these formal insertion reactions remained obscure. Such fundamental reactions have a direct bearing on the role of gold catalysts in organic transformations 10, 11, 12…”
mentioning
confidence: 99%
“…The bond lengths C17-Au 1.989 (8) represent genuine interactions or a merely a chance consequence of the sterically exposed nature of two-coordinate gold atoms [64].…”
Section: Compound 17mentioning
confidence: 99%